(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
The article analyzes the evolution of French defense policy from the Cold War to the present day. After presenting the country’s strategic outlook during the Cold War, the article studies the White Papers drawn up by France to adapt its national defense and military organization to the changing domestic and international situation. Viewed as a whole, they show the profound transformations French defense policy has experienced over the last decades